Meeting students' special needs in Catholic schools: a report from the USA. Issue 1 (2nd January 2017) - Scanlan, Martin
Abstract : Students experience a wide array of special needs, from diagnosed disabilities to cultural and linguistic barriers to traumas. Schools around the world and across public and private sectors struggle to provide optimal opportunities to learn for students experiencing special needs. Moreover, schools typically engage in these efforts in isolation from one another. This article suggests a way to foster greater collaboration to reduce this variation and promote sustained improvement in how schools meet students' special needs. It applies 'improvement science' as a conceptual framework that can guide efforts to address this problem, and focuses on one sector, Catholic schools, which is growing internationally and shares a philosophy of education that places a preferential option on traditionally marginalised students.